The effect of added calcium and phosphorus with and without added protein in the ration of steers on bluestem pasture - Drake, C.L.; Smith, E.F.; Richardson, D.; Tsien, W.S. (Kansas Agricultural Experiment Station, 2011)
This experiment was designed to evaluate the desirability of supplementing bluestem pasture as indicated in the title. Forty Hereford steer calves were divided into four lots of 10 each and fed the following rations per head daily: Lot 1. Two pounds of dehydrated molasses (a molasses product dried on soybean hulls). Lot 2. Two pounds of dehydrated molasses and 39.1 grams of dicalcium phosphate. Lot 3. One pound of dehydrated molasses and 1 pound of 41% corn gluten meal. Lot 4. One pound of dehydrated molasses and 1 pound of 41% corn gluten meal plus 29.6 grams of dicalcium phosphate.
Keywords: Beef; Calcium; Phosphorus; Protein; Bluestem pasture; Steers